2019
DOI: 10.1186/s12938-019-0689-3
|View full text |Cite|
|
Sign up to set email alerts
|

Proposal of a new conceptual gait model for patients with Parkinson’s disease based on factor analysis

Abstract: Background Gait impairment is a risk factor for falls in patients with Parkinson’s disease (PD). Gait can be conveniently assessed by electronic walkways, but there is need to select which spatiotemporal gait variables are useful for assessing gait in PD. Existing models for gait variables developed in healthy subjects and patients with PD show some methodological shortcomings in their validation through exploratory factor analysis (EFA), and were never confirmed by confirmatory factor analysis (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 76 publications
(198 reference statements)
2
31
0
Order By: Relevance
“…Factor analysis effectively reduced the dimensionality of our dataset from twenty-five gait parameters to four independent domains of gait. Factors reflecting the spatial and temporal aspects of gait speed are consistently reported in literature [32][33][34][35][36] . Other factors related to gait reported in literature are variability 32,33,35,36 , asymmetry 33,35,36 , postural control 33 , and trunk motion 34 .…”
Section: Discussionmentioning
confidence: 75%
“…Factor analysis effectively reduced the dimensionality of our dataset from twenty-five gait parameters to four independent domains of gait. Factors reflecting the spatial and temporal aspects of gait speed are consistently reported in literature [32][33][34][35][36] . Other factors related to gait reported in literature are variability 32,33,35,36 , asymmetry 33,35,36 , postural control 33 , and trunk motion 34 .…”
Section: Discussionmentioning
confidence: 75%
“…This could be related to the reduction in muscle power, loss of distal proprioception and vision seen with age [157,158]. In addition, it has been suggested that step length is controlled by the cortico-basal ganglia circuit [159], and there is evidence that gait speed is specifically linked to the frontoparietal control network, which is critically involved in executive function [160]. Decreased executive function has been associated with decreased gait speed due to decreased stride length, together with increased stride length variability in elderly with mild cognitive impairment [161].…”
Section: Gait Variabilityeffect Of Pd-pathology and Agementioning
confidence: 99%
“…Swing time variability was defined as the mean swing time coefficient of variation (CV = standard deviation/mean) and was averaged between legs. A larger swing time CV is indicative of more variable gait and has been shown to be independent of gait speed and shows high reliability (Arcolin et al, 2019;Frenkel-Toledo et al, 2005). Data were log transformed to conform to normality.…”
Section: Kinetic Data Acquisition and Analysismentioning
confidence: 99%